2021
DOI: 10.1007/s00068-021-01645-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical-pathological features and treatment of acute appendicitis in the very elderly: an interim analysis of the FRAILESEL Italian multicentre prospective study

Abstract: Background emergency abdominal surgery in the elderly represents a global issue. Diagnosis of AA in old patients is often more di cult. Appendectomy remains the gold standard of treatment and, even though it is performed almost exclusively with a minimally invasive technique, it can still represent a great risk for the elderly patient, especially above 80 years of age. A careful selection of elderly patients to be directed to surgery is therefore fundamental. The primary aim was to critically appraise and comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The collected data includes demographics, duration of pre-hospitalization symptoms, American Society of Anesthesiologists risk score(ASA score) ( 14 ), preparative times of pre-operation, operation time, surgical findings, surgical approach, LOS, postoperative complications, pathology reports, 30-day readmission rate, and vaccination status(receive at least one dose of vaccination). The appendicitis inflammatory response (AIR) scores were calculated based on the collected data ( 15 ).…”
Section: Data Collectionmentioning
confidence: 99%
“…The collected data includes demographics, duration of pre-hospitalization symptoms, American Society of Anesthesiologists risk score(ASA score) ( 14 ), preparative times of pre-operation, operation time, surgical findings, surgical approach, LOS, postoperative complications, pathology reports, 30-day readmission rate, and vaccination status(receive at least one dose of vaccination). The appendicitis inflammatory response (AIR) scores were calculated based on the collected data ( 15 ).…”
Section: Data Collectionmentioning
confidence: 99%
“…In the CFS group a small prospective observational study by Goeteyn et al reported a mean length of stay of 14.6 days which was distributed evenly in both frail and non-frail groups ( p = 0.597) ( 21 ). On the other hand, Li et al observed a median LOS 7 days ( 4 11 ) in the non-frail group compared to 13 days (7.5–27.5) in the frail ( p < 0.001) ( 31 ). The pooled weighted difference in in the CFS subgroup was 4.15 days (CI: −0.21–8.51; p = 0.062).…”
Section: Resultsmentioning
confidence: 95%
“…It is well-known that ASA (PS) (American Society of Anesthesiologists Physical Status Classification System) score 3 or above is an independent predictor of unfavorable outcomes not just in elective but more so in emergency surgery ( 3 ). Furthermore, older age, male sex, peritoneal contamination, use of oral anticoagulant, need for blood transfusion, hypoalbuminemia and electrolyte abnormalities (potassium and sodium) have a negative influence on the success rate of emergency surgical interventions ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, adverse outcomes have been reported regardless of the time elapsed from the surgical procedure if reasonably related to it and occurred during the hospitalization following the main emergency procedure. The cut-off adopted for CACI, 5-mFI, and EmSFI, and the choice to consider C-D complication ≥2 derives from both literature and our previous already published statistical analysis ( 34 ). The primary aim was to critically appraise the influence of MetS with or without SIRS, and with or without frailty in the elderly undergoing emergency surgical procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Although advances in surgical techniques, anaesthetic procedures, and postoperative care have all made surgery less hazardous, surgeons are generally more reluctant to operate on elderly patients because they are perceived to be frail, to have less physiological reserve, and to have more underlying medical conditions ( 1 3 ). Several factors are thought to relate to the postoperative outcome ( 4 , 5 ). Metabolic syndrome (MetS) is a combination of risk factors that include high blood pressure, dyslipidaemia (high triglyceride and low high-density lipoprotein–cholesterol concentrations), high fasting glucose concentration, and central obesity ( 6 – 9 ).…”
Section: Introductionmentioning
confidence: 99%